Check poets named because the Mokhazram - Feali, Behnam; Reza Beigi, Mohammad; Nazari, Behnaz (Pure and Applied Science Advances, 2014)
Mokhazram meaning of the word (Alkhazrameh) is. The cut and design of the finishing period and the beginning of another era. Mokhazram poet, in terms of literary history that someone half his life in ignorance and the other half is understood in Islam and in both the poetry is written. In the early days of the revelation of the Quran, in all aspects of life, the impact has been undeniable. Poets are both ignorant and of course understand, and Mokhazram known poets. In this paper, the aim is that the poets named in it, and the periods in which they have lived, studied and be familiar with these poets. This group of poets, through his poetry, and religious themes and meanings of the sublime, pointed, and witnessed the changing themes of the poem are ignorant, and of the Holy Quran and the Prophetic Hadith effect, and the poetry and have used their prose.